Predictability of inter-regional cerebral perfusion similarity on dopamine responsiveness and the moderation role of cognition in PD patients - Cao, Zhengye; Wu, Chenqing; Hong, Hui; Huang, Peiyu; Zhou, Cheng; Guan, Xiaojun; Wu, Haoting; Duanmu, Xiaojie; Xu, Xiaojun; Zhang, Minming (NeuroImage (Orlando, Fla.), 2023)
•Based on the constructed intra-individual CBF relative variation network, significant alterations caused by dopamine depletion could be reflected.•Off-state inter-regional CBF perfusion similarity was found that had a significant influence on dopamine responsiveness of PD patient.•PD patient's cognitive status positively moderated the relationship between off-state inter-regional CBF perfusion similarity and dopamine responsiveness. And significant main effect of cognition on dopamine responsiveness could be observed. Large heterogeneity can be found in dopamine responsiveness of patients with Parkinson's disease (PD). Instantly and objectively understanding dopamine responsiveness of patients may help clinical practice. This PD study explored the predictability of off-state inter-regional cerebral blood flow (CBF) perfusion similarity on patient's dopamine responsiveness and tested whether the predictive power could be moderated by patient's cognitive status. The PD cohort with 192 patients (containing off state and on state (PD-off and PD-on)) and the normal control (NC) cohort with 92 subjects were included. The intra-individual CBF relative variation networks were constructed and compared between PD-off and PD-on, PD-off and NC to identify the alterations caused by dopamine depletion. Based on that, regression analysis of off-state inter-regional CBF perfusion similarity on patient's dopamine responsiveness was performed. Finally, moderation analysis was conducted to test the moderation role of cognition on the regression model. In the PD-off cohort, a total of 82 edges in the network were identified that affected by dopamine depletion. Off-state inter-regional CBF perfusion similarity was found that had a significant influence on patient's dopamine responsiveness. Cognitive status was validated that positively moderated the relationship between off-state inter-regional CBF perfusion similarity and dopamine responsiveness. Dopamine responsiveness of PD patient could be predicted by off-state inter-regional CBF perfusion similarity. Patient's cognitive status might have a positive moderation effect on his/her dopamine responsiveness.